AtRsgA from Arabidopsis thaliana is important for maturation of the small subunit of the chloroplast ribosome. (8th September 2018) - Janowski, Marcin; Zoschke, Reimo; Scharff, Lars B.; Martinez Jaime, Silvia; Ferrari, Camilla; Proost, Sebastian; Ng Wei Xiong, Jonathan; Omranian, Nooshin; Musialak‐Lange, Magdalena; Nikoloski, Zoran; Graf, Alexander; Schöttler, Mark A.; et al.
Summary: Plastid ribosomes are very similar in structure and function to the ribosomes of their bacterial ancestors. Since ribosome biogenesis is not thermodynamically favorable under biological conditions it requires the activity of many assembly factors. Here we have characterized a homolog of bacterial RsgA in Arabidopsis thaliana and show that it can complement the bacterial homolog. Functional characterization of a strong mutant in Arabidopsis revealed that the protein is essential for plant viability, while a weak mutant produced dwarf, chlorotic plants that incorporated immature pre‐16S ribosomal RNA into translating ribosomes. Physiological analysis of the mutant plants revealed smaller, but more numerous, chloroplasts in the mesophyll cells, reduction of chlorophyll a and b, depletion of proplastids from the rib meristem and decreased photosynthetic electron transport rate and efficiency. Comparative RNA sequencing and proteomic analysis of the weak mutant and wild‐type plants revealed that various biotic stress‐related, transcriptional regulation and post‐transcriptional modification pathways were repressed in the mutant. Intriguingly, while nuclear‐ and chloroplast‐encoded photosynthesis‐related proteins were less abundant in the mutant, the corresponding transcripts were increased, suggesting an elaborate compensatory mechanism, potentially via differentially active retrograde signaling pathways. To conclude, this study reveals a chloroplast ribosome assembly factor and outlines the transcriptomic and proteomic responses of the compensatory mechanism activated during decreased chloroplast function. Significance Statement: AtRsgA is an assembly factor necessary for maturation of the small subunit of the chloroplast ribosome. Depletion of AtRsgA leads to dwarfed, chlorotic plants, a decrease of mature 16S rRNA and smaller, but more numerous, chloroplasts. Large‐scale transcriptomic and proteomic analysis revealed that chloroplast‐encoded and ‐targeted proteins were less abundant, while the corresponding transcripts were increased in the mutant. We analyze the transcriptional responses of several retrograde signaling pathways to suggest the mechanism underlying this compensatory response.